Retention efficiency for microplastic in a landscape estimated from empirically validated dynamic model predictions - Norling, Magnus; Hurley, Rachel; Schell, Theresa; Futter, Martyn N; Rico, Andreu; Vighi, Marco; Blanco, Alberto; Ledesma, José L J; Nizzetto, Luca (Journal of hazardous materials, 2024)
Soils are recipients of microplastic that can be subsequently transferred to the sea. Land sources dominate inputs to the ocean, but knowledge gaps about microplastic retention by land hinder assessments of input rates. Here we present the first empirical evaluation of a dynamic microplastic fate model operating at landscape level. This mechanistic model accounts for hydrology, soil and sediment erosion, particle characteristics and behavior. We predict microplastic concentrations in water and sediments of the Henares river (Spain) within the measurement uncertainty boundaries (error factors below 2 and 10, respectively). Microplastic export from land and discharge by river fluctuates in a non-linear manner with precipitation and runoff variability. This indicates the need of accurate dynamic descriptions of soil and stream hydrology even when modeling microplastic fate and transport in generic scenarios and at low spatio-temporal resolution. A time-averaged landscape retention efficiency was calculated showing 20-50% of the microplastics added to the catchment over a multiannual period were retained. While the analysis reveals persistent uncertainties and knowledge gaps on microplastic sources to the catchment, these results contribute to the quantitative understanding of the role of terrestrial environments in accumulating microplastics, delaying their transport to the sea.
Keywords: Fate and transport; Model; Soil; Microplastics; River